Exploração sexual comercial: uma análise da legislação e da jurisprudência do Superior Tribunal de Justiça nos caos de crianças e adolescentes submetidas a prostituição - Melo, Alexandre Soares de (2013)
Sexual and commercial explotation of children and adolescents is a social phenomenon which, nowadays, has found vast regulation in Brazilian law. According to the article 244-A of Child and Adolescent Statute and the article 218-B of Brazilian Penal Code it is considered a crime the conduct of submitting or favoring children and adolescents to prostitution or other forms of exploitation. However, there is a great controversy both in terms of doctrine and jurisprudence from the Brazilian Court of Justice in relation to establishing if the criminal responsibility in these cases would not only be upon the agents and allucers who intermediate the sexual practice, as ponces and ruffians, but if it would also extend to those users who, without the intermediation of others, keep sexual contact with children and adolescents who are included in a context of prostitution. Thus, the object of this study consists in the analyses of the criminal responsibility of the violations related to sexual exploitation of prostituted children and adolescents. Our aim is to understand the present mainstream legal argument in the jurisprudence of Brazilian Superior Court of Justice in order to establish the extent of the penal norm as well as the criminal responsibility of the agents involved. The understanding of the factors which favor the sexual exploitation of children and adolescents, such as social inequality, sexual mercantilization and the asymmetrical genders relationships in our society are presented as important instruments for analyses of the legal argument in the scope of the courts as well as for the strength of the child and adolescent protection system in this country. This research has an empirical nature and has been based on a legislation and specialized literature review about this theme.